A Hybrid Imaging Platform(CT/PET/FMI) for Evaluating Tumor Necrosis and Apoptosis in Real-Time - Kang, Yulin; Zhai, Xiaohui; Lu, Sifen; Vuletic, Ivan; Wang, Lin; Zhou, Kun; Peng, Zhiqiang; Ren, Qiushi; Xie, Zhaoheng (Frontiers in Oncology, 2022)
Multimodality imaging is an advanced imaging tool for monitoring tumor behavior and therapy in vivo. In this study, we have developed a novel hybrid tri-modality system that includes two molecular imaging methods: positron emission computed tomography (PET) and fluorescence molecular imaging (FMI) and the anatomic imaging modality X-ray computed tomography (CT). The following paper describes the system development. Also, its imaging performance was tested in vitro (phantom) and in vivo, in Balb/c nude mice bearing a head and neck tumor xenograft treated with novel gene therapy [a new approach to the delivery of recombinant bacterial gene (IL-24-expressing strain)]. Using the tri-modality imaging system, we simultaneously monitored the therapeutic effect, including the apoptotic and necrotic induction within the tumor in vivo. The apoptotic induction was examined in real-time using an 18F-ML-10 tracer; the cell death was detected using ICG. A CT was used to evaluate the anatomical situation. An increased tumor inhibition (including tumor growth and tumor cell apoptosis) was observed in the treatment group compared to the control groups, which further confirmed the therapeutic effect of a new IL-24-expressing strain gene therapy on the tumor in vivo. By being able to offer concurrent morphological and functional information, our system is able to characterize malignant tissues more accurately. Therefore, this new tri-modality system (PET/CT/FMI) is an effective imaging tool for simultaneously investigating and monitoring tumor progression and therapy outcomes in vivo.